Epidermal Growth Factor Receptor Mutation Enhances Expression of Cadherin-5 in Lung Cancer Cells - Hung, Ming-Szu (PLoS One, 2016)
Epidermal growth factor receptor (EGFR) activation has been shown to play a critical role in tumor angiogenesis. In this study, we investigate the correlation between EGFR mutations and cadherin-5 (CDH5), which is an angiogenic factor, in lung cancer cells. Increased expression CDH5 is observed in lung cancer cells with EGFR mutations. Stable lung cancer cell lines expressing mutant (exon 19 deletion E746-A750, and exon 21 missense mutation L858R) and wild type EGFR genes are established. A significantly higher expression of CDH5 is observed in exon 19 deletion stable lung cancer cells and mouse xenografts. Further studies show that expression of CDH5 is decreased after the inhibition of EGFR and downstream Akt pathways in lung cancer cells with EGFR mutation. In addition, mutant EGFR genes potentiates angiogenesis in lung cancer cells, which is inhibited by CDH5 siRNA, and potentiates migration and invasion in lung cancer cells. Our study shows that mutant EGFR genes are associated with overexpression of CDH5 through increased phosphorylation of EGFR and downstream Akt pathways. Our result may provide an insight into the association of mutant EGFR and CDH5 expression in lung cancer and aid further development of target therapy for NSCLC in the future.